Comparative evaluation of two intranasal forms of Curcumin: Quantitation and impact on mouse model of asthma - Payal Singh; Ruchi Chawla; Ajai Kumar Pandey; J.K. Mishra; Rashmi Singh (Elsevier, 2023)
Aim of the study: Present study aimed to investigate impact of two different intranasal forms of curcumin on mouse model of asthma and detection of its absorption after different time points of administration. Since the systemic bioavailability of curcumin is very low, therefore, intranasal route of administration has been explored here where systemic absorption of two intranasal forms of curcumin was evaluated. Materials and methods: To explore the possibilities of its absorption and role in amelioration of asthma, two intranasal forms of curcumin, nasal drop and aerosol were administered to control and asthmatic mice. Blood plasma and lungs were collected at different time points of curcumin administration. Separation was done by using isocratic reversed phase high performance liquid chromatography (HPLC). Airway inflammation and oxidative stress parameters like SOD, Catalase, ROS, lipid peroxidation, and total inflammatory cell recruitments were analyzed to study efficacy of two intranasal forms of curcumin. Results: Maximum absorption was noted at 3 hrs of different intranasal forms of curcumin, administration, i.e., nasal drop (1.93 ± 0.050 plasma, 2.87 ± 0.26 in lungs) and aerosol form of curcumin where better absorption was noted in aerosol form as compared to nasal drop (Lungs 3.08 ± 0.12 aerosol, 2.05 ± 0.020 nasal drop) at 1 h. Both, curcumin aerosol and nasal drops were effective in ameliorating oxidative stress (p < 0.05) associated with asthma in mice model. The present study may pave the way towards the development of intranasal curcumin as complementary medication because of its better absorption in plasma and lungs.